Conservation of the sporozoite p67 vaccine antigen in cattle-derived Theileria parva stocks with different cross-immunity profiles - Nene, Vishvanath M.; Musoke, A.J.; Gobright, E.I.; Morzaria, S.P. (1996)
Immunity to Theileria parva infection in cattle is often parasite stock specific. The antigenic diversity which is expressed at the schizont stage of the parasite together with a wild reservoir of the organism in buffalo has complicated the development of effective disease control by immunization. We have previously shown that about 70 percent of cattle inoculated with recombinant forms of p67, a sporozoite stage-specific surface antigen from the cattle-derived Muguga stock of the parasite, are immune to a homologous challenge. Thus, immune responses to p67 can play a role in immunity. The genes encoding this protein in five other parasite stocks have been sequenced. here, we report that the p67 molecule encoded by four cattle-derived parasite stocks (Boleni, Uganda, Mariakani, and Marikebuni) that fall into different cross-immunity groups is identical in sequence to Muguga p67. the protein encoded by a buffalo-derived parasite exhibits 95 percent sequence identity with Muguga p67, the major difference being the presence of a 43-residue peptide insert. As predicted by these data, cattle inoculated with recombinant p67 can resist a heterologous cattle-derived parasite challenge. Seven of 12 cattle receiving a homologous Muguga challenge and 6 of 11 cattle receiving a heterologous Marikebuni challenge were immune to East Coast fever. These results extend earlier data suggesting that p67 is a conserved molecule and confirm its potential as a broad-spectrum vaccine antigen for the control of T. parva infection.